Gopher - University of Minnesota. Junior Class; University of Minnesota. Senior Class (Minneapolis, Minn. Frank S. Lewis, 1888)
Annual
Published annually by the Junior Class of the University of Minnesota, 1889-1929; by its Senior Class, 1930-
Title varies slightly.
Keywords: University of Minnesota